2014
DOI: 10.1371/journal.pone.0091111
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Ameliorates Hepatic Steatosis and Inflammation without Altering Adipose Phenotype in Diet-Induced Obesity

Abstract: Non-alcoholic fatty liver disease (NAFLD) is closely associated with obesity and insulin resistance. To better understand the pathophysiology of obesity-associated NAFLD, the present study examined the involvement of liver and adipose tissues in metformin actions on reducing hepatic steatosis and inflammation during obesity. C57BL/6J mice were fed a high-fat diet (HFD) for 12 weeks to induce obesity-associated NAFLD and treated with metformin (150 mg/kg/d) orally for the last four weeks of HFD feeding. Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
113
3
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(132 citation statements)
references
References 49 publications
12
113
3
4
Order By: Relevance
“…Thus, metformin is not recommended as a specific treatment for NAFLD in clinical practice guidelines (Chalasani et al 2012). By contrast, the data based on animal studies have shown that metformin improves hepatic steatosis, liver inflammation, and to a certain degree fibrosis (Lin et al 2000, Woo et al 2014, Tripathi et al 2015. These results are consistent with the data of this study.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, metformin is not recommended as a specific treatment for NAFLD in clinical practice guidelines (Chalasani et al 2012). By contrast, the data based on animal studies have shown that metformin improves hepatic steatosis, liver inflammation, and to a certain degree fibrosis (Lin et al 2000, Woo et al 2014, Tripathi et al 2015. These results are consistent with the data of this study.…”
Section: Discussionsupporting
confidence: 88%
“…The main molecular mediator of these effects is regarded as adenosine monophosphate-activated protein kinase (AMPK) (Browning & Horton 2004, Woo et al 2014, Zheng et al 2015. By activation of AMPK, metformin improved hepatic lipid metabolism via decreasing activities of ACC-1 and hydroxymethylglutarylcoenzyme A (HMG-CoA) reductase, promoting β-oxidation, and inhibiting SREBP 1-c, a master transcription factor that induces the expression of lipogenic genes including FAS , leading to decreased steatosis levels.…”
Section: Discussionmentioning
confidence: 99%
“…The direct anti-inflammatory action of metformin has been reported in several animal experimental studies, both in the liver (69,54,47) and in circulating polymorphonuclear cells (9). In contrast to these experimental findings, metformin efficiency in human NASH treatment is the subject of open debate (58,60).…”
Section: Discussionmentioning
confidence: 99%